2013
DOI: 10.1016/j.neuroscience.2013.03.058
|View full text |Cite
|
Sign up to set email alerts
|

Periadolescent ethanol vapor exposure persistently reduces measures of hippocampal neurogenesis that are associated with behavioral outcomes in adulthood

Abstract: Excessive alcohol consumption is prevalent among adolescents and may result in lasting neurobehavioral consequences. The use of animal models to study adolescent alcohol exposure has the advantage of allowing for the control necessary in order to evaluate the effects of ethanol on the brain and separate such effects from genetic background and other environmental insults. In the present study the effects of moderate ethanol vapor exposure, during adolescence, on measures of neurogenesis and behavioral measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
100
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(111 citation statements)
references
References 89 publications
11
100
0
Order By: Relevance
“…We suggest that the observation of increases in entries and time spent in the open arms is consistent with an increase in impulsivity. This is also consistent with a recent report using a modified open field conflict task in which it was observed that adult AIE exposed rats displayed more disinhibitory behavior compared to non-alcohol exposed control rats (Ehlers et al , 2013a). As with the EPM, the possibility that the rats were exhibiting less anxiety-like behavior on this task cannot be excluded.…”
Section: Discussionsupporting
confidence: 93%
“…We suggest that the observation of increases in entries and time spent in the open arms is consistent with an increase in impulsivity. This is also consistent with a recent report using a modified open field conflict task in which it was observed that adult AIE exposed rats displayed more disinhibitory behavior compared to non-alcohol exposed control rats (Ehlers et al , 2013a). As with the EPM, the possibility that the rats were exhibiting less anxiety-like behavior on this task cannot be excluded.…”
Section: Discussionsupporting
confidence: 93%
“…For instance, early adolescents demonstrate more pronounced ethanol-induced damage in anterior cortical regions than their older counterparts following 4 days of exposure to high ethanol daily doses of 9–10 g/kg (Crews, Braun, Hoplight, Switzer, & Knapp, 2000), and repeated (Ehlers, Liu, Wills, & Crews, 2013) as well as acute adolescent exposure to ethanol has been reported to effectively inhibit neurogenesis in these immature animals (Crews, Mdzinarishvili, Kim, He, & Nixon, 2006). Alterations are also evident in the glutamatergic (Guerri & Pascual, 2010; Pascual, Boix, Felipo, & Guerri, 2009) and gamma-aminobutyric acid systems (Falco, Bergstrom, Bachus, & Smith, 2009; Fleming, Acheson, Moore, Wilson, & Swartzwelder, 2012) – neural systems that play a substantial role in modulation of social behavior (Morales, Varlinskaya, & Spear, 2013a,b; Silvestre, Nadal, Pallarés, & Ferré, 1997; Siviy, Line, & Darcy, 1995) and anxiety-like behavioral alterations (Atack, 2005; Möhler, 2012; Trincavelli, Da Pozzo, Daniele, & Martini, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, adult hippocampal neurogenesis is resilient, recovering over a 30-day period from the 4-day binge alcohol model (Nixon & Crews, 2004) and a 7-week chronic prolonged relapsing model of alcohol dependence, whereas the ventricular neurogenesis is persistently reduced (Hansson et al, 2010). In contrast, in models of underage drinking (e.g., adolescent intermittent ethanol (AIE) treatment), hippocampal neurogenesis is persistently inhibited into adulthood (Broadwater, Liu, Crews, & Spear, 2013; Ehlers, Liu, Wills, & Crews, 2013). AIE exposure reductions in neurogenesis were found to be associated with more “disinhibitory” behavior in the open field conflict test at 2 and 8 weeks following termination of vapor exposure (Ehlers, Liu, et al, 2013).…”
Section: Loss Of Neurogenesis Could Contribute To Alcoholic Neurodmentioning
confidence: 99%
“…In contrast, in models of underage drinking (e.g., adolescent intermittent ethanol (AIE) treatment), hippocampal neurogenesis is persistently inhibited into adulthood (Broadwater, Liu, Crews, & Spear, 2013; Ehlers, Liu, Wills, & Crews, 2013). AIE exposure reductions in neurogenesis were found to be associated with more “disinhibitory” behavior in the open field conflict test at 2 and 8 weeks following termination of vapor exposure (Ehlers, Liu, et al, 2013). Similarly, AIE exposure of rats found reduced hippocampal volumes assessed using MRI consistent with those found in alcoholism (Ehlers, Oguz, Budin, Wills, & Crews, 2013).…”
Section: Loss Of Neurogenesis Could Contribute To Alcoholic Neurodmentioning
confidence: 99%